Intelligent Task Recognition: Towards Enabling Productivity Assistance in Daily Life - Liono, Jonathan; Rahaman, Mohammad Saiedur; Salim, Flora D; Ren, Yongli; Spina, Damiano; Scholer, Falk; Trippas, Johanne R; Sanderson, Mark; White, Ryen W.; Bennett, Paul (2020 International Conference on Multimedia Retrieval, 2020)
We introduce the novel research problem of task recognition in daily life. We recognize tasks such as project management, planning, meal-breaks, communication, documentation, and family care. We capture Cyber, Physical, and Social (CPS) activities of 17 participants over four weeks using device-based sensing, app activity logging, and an experience sampling methodology. Our cohort includes students, casual workers, and professionals, forming the first real-world context-rich task behaviour dataset. We model CPS activities across different task categories, results highlight the importance of considering the CPS feature sets in modelling, especially work-related tasks.